The IMF crisis of 1976 and British politics - Hickson, Kevin (International library of political studies, 2005)
The IMF crisis of 1976 was a seminal event in British political history, with the government seen as going 'cap in hand' to the International Monetary Fund in order to avert financial meltdown. This text uses original source material in order to identify the economic thought and practice which caused the crisis.